PENGARUH PEMANFAATAN MEDIA SOSIAL, MODAL USAHA, DAN PEMAHAMAN AKUNTANSI TERHADAP KEBERLANJUTAN BISNIS UMKM DI MASA PANDEMI COVID-19 DI KOTA BATU - Wahyu Zakiyah Faradillah; Maslichah Maslichah; Afifudin Afifudin (Universitas Islam Malang, 2022)
This study aims to determine the effect of using social media, business capital, and understanding of accounting on the sustainability of UMKM business during the Covid-19 pandemic in Batu City. The independent variable in this study is the use of social media, business capital, and accounting understanding, while the dependent variable is the sustainability of the UMKM business during the Covid-19 pandemic in Batu City. This type of research is quantitative research, because the data used are in the form of numbers and numbers. The source of data in this study is primary data with the data collection method in the form of a questionnaire. The population in this study were MSME actors registered at the Office of Cooperatives, Micro Enterprises, Industry and Trade in Batu City. The data collection technique uses the slovin formula. Based on this method, the number of MSME actors used was 100 respondents. The hypotheses were tested using descriptive statistical analysis, instrument testing, normality test, classical assumption test, multiple linear regression analysis test, and hypothesis testing using SPSS Version 22. The results showed that the variable of social media utilization had a positive and significant impact on the sustainability of MSME business. (0.000 < 0.05), while the business capital variable has no effect on the sustainability of the MSME business (0.569 > 0.05), and the accounting understanding variable has a positive and significant effect on the MSME business sustainability (0.008 < 0.05). Keywords: use of social media, business capital, understanding of accounting, UMKM business sustainability.